Sodium dodecylbenzene sulphonate (SDBS) present in detergents: action on the gills, skin, and blood of D. rerio fish - Santos, Eduardo Libanio Reis [UNESP]; Silva, Odaiza [UNESP]; Oliveira-Lima, Jeffesson de; Camargo-Mathias, Maria Izabel [UNESP] (Taylor & Francis, 2024)
1. Sodium dodecylbenzene sulphonate (SDBS) is one of the surfactants used worldwide in detergents which, due to high residual discharges, has great potential to cause ecotoxicological impacts. Therefore, the sublethal effects of SDBS on the gills and skin of male Danio rerio fish were investigated. 2. The fish were distributed into three groups: GC (control), GT1 (0.25 mg/L of SDBS), and GT2 (0.5 mg/L of SDBS) and exposed for 21 days. After the experiment, histopathological analyses of the gills, histochemical analyses (counting of mucous cells), and biochemical analyses (antioxidant defense enzyme analysis, SOD, and CAT) were conducted. 3. A significant increase (p < 0.05) in the incidence of circulatory disorders, progressive, and regressive alterations occurred in the GT1 and GT2 groups. Due to these changes, the total histopathological index of the gills was higher in these groups. Mucous cells in the gills and skin increased. There was an increase in SOD activity and a reduction in CAT activity in these groups. Haematology revealed neutrophilia and lymphocytosis in the blood of GT1 and GT2. 4. The results clearly demonstrate that a 21-day exposure to SDBS causes severe morphophysiological damage to the gills, skin, and blood of D. rerio fish.
Keywords: Anionic surfactant; glycoproteins; haematology; histopathological damage; oxidative stress; zebrafish